Enzymatic interesterification, fractional crystallisation and its physicochemical properties of palm-based cocoa butter equivalent with high palmitoyl-oleoyl-stereoyl level - Mohamad Alwi, Siti Maslina (2018)
Cocoa butter is important in the confectionary industry because of its organoleptic attributes. This fat provides cool melting in the mouth sensation that gives a satisfying feeling to whoever eats chocolate. Cocoa butter was made from cocoa beans which undergo processes such as, drying, roasting, refining and fractionation. The end products, namely cocoa butter, cocoa liquor and cocoa mass are used mainly for chocolate industry. However, the supply and price of cocoa butter seems to deteriorate over the years, alluring researchers to study and produce alternatives to cocoa butter. Even though exotic fats are available as Cocoa Butter Equivalents, they also have instability issues as cocoa butter. Therefore, palm oil, rich in palmitic acids is explored to be one of the alternatives. In this study, crude palm-based cocoa butter equivalent (CBE) was developed via enzymatic interesterification between palm-based fat and fully hydrogenated fat. Fully hydrogenated fat with low Iodine Value used as the stearic donor to obtain high levels of POS (1-palmitoyl-2-oleoyl-3-stearoyl-sn-glycerol) triacylglycerols. Response Surface Methodology was used to obtain the optimum percentage of POS response of the interesterified product. The major parameters that influence the enzymatic interesterification reactions such as substrate ratio Palm Oil: Fully Hydrogenated Palm Oil (50:50-100:0 w/w), temperature (65-75°C), incubation time (30-600 minutes) and enzyme load (2-12 % w/w) were used for optimization. Based on the highest yield of POS produced using RSM, the optimal enzymatic parameters were: ratio of palm oil/fully hydrogenated palm oil is 1:1, 9.5% of enzyme load, 172.5 minute of retention time at 63.75°C. To purify the fat, the enzymatic interesterified product was subjected to fractionation process at various cooling temperatures (32-45°C) and reaction time (12-36 hour). At 34°C, POS achieved at the highest level which was approximately 31% after 12 hour of cooling process. The study of physiochemical properties of the CBE fat were done for characterization identification. The properties were solid fat content, slip melting point and iodine value. The Iodine Value (IV) and Slip Melting Point (SMP) are 44.30 and 29°C, respectively. Physicochemical characteristics of Cocoa butter Equivalent fractionated at 34°C (CBE34) fat proposed that it could be utilized in confectionery industry as CBE. Though the CBE produced was slightly softer compared to Cocoa Butter (CB), it fulfills the growing trend of softer chocolates that quickly dissolves in the mouth. The characteristics of the CBE produced, having high yield of POS contributed to the compatibility with CB. The thermo profile indicated that CBE34 fat melted below body temperature (37°C), which contributes to the fast melting in the mouth, leaving no waxy taste. According to European Union regulations, only 5% of CBE can be used in chocolate formulations, therefore, CBE34 will be easily blended with CB. The crystallization profile of CBE34 is (β'+β), which is similar to cocoa butter. Hence, from this study, CBE 34 is recommended for utilization in the confectionery industry as CBE.